2020
DOI: 10.2528/pierc19091105
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Characteristics of Hybrid Excitation Double Stator Bearingless Switched Reluctance Motor

Abstract: In order to research the temperature distribution of a hybrid excitation double stator bearingless switched reluctance motor (HEDSBSRM), the finite element method (FEM) is used to conduct thermal modeling and analysis. First, 2D FEM is used to calculate the losses of the motor, including the core losses and copper losses of the windings. Then, in the thermal analysis module of ANSYS Workbench software, losses are used for calculation and analysis as the thermal load. Furthermore, in order to enhance the accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Reference [15] analyzed thermal performance of a 10 kw double stator switched reluctance motor at various load conditions and concluded that the temperature of inner stator is higher than outer stator because of the cooling system. Establish transient model with finite element method (FEM) to calculate the loss of BSRM and then import the loss as heat source into thermal field to analyze the temperature distribution of the motor [16][17][18]. There are more and more researches on the control strategy, parameter design, and vibration noise reduction of BSRM [19][20][21], but little research on the change of body heat when the motor is running.…”
Section: Introductionmentioning
confidence: 99%
“…Reference [15] analyzed thermal performance of a 10 kw double stator switched reluctance motor at various load conditions and concluded that the temperature of inner stator is higher than outer stator because of the cooling system. Establish transient model with finite element method (FEM) to calculate the loss of BSRM and then import the loss as heat source into thermal field to analyze the temperature distribution of the motor [16][17][18]. There are more and more researches on the control strategy, parameter design, and vibration noise reduction of BSRM [19][20][21], but little research on the change of body heat when the motor is running.…”
Section: Introductionmentioning
confidence: 99%
“…introduced another dimension to the discourse, emphasising the resilience of VC-backed IPOs, which showcased significantly reduced failure rates. Delving deeper into the organisational structure,Howton (2006) andJain and Kini (2008) highlighted the pivotal role of internal governance mechanisms, such as CEO ownership, board composition, and tenure, in influencing IPO survival Feng et al (2020). broadened the scope by emphasising firms' strategic orientations, asserting that market and entrepreneurial orientations serve as catalysts for IPO longevity Kooli and Meknassi (2007).…”
mentioning
confidence: 99%